2002
DOI: 10.1007/s10350-004-6116-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhoidectomy: Open or Closed Technique?

Abstract: Although the healing time is longer, the open technique is more advantageous with respect to shorter operating time, less discomfort in the early postoperative period, and lower morbidity rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(19 citation statements)
references
References 14 publications
2
14
1
2
Order By: Relevance
“…[3][4][5] While these various approaches involve different techniques and instruments, there is no evidence for significant differences in the results obtained between closed and open hemorrhoidectomies. 6,7 In any surgical management of hemorrhoids, postoperative pain is the most common complaint. 8 In particular, internal sphincter spasm is usually associated with pain.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] While these various approaches involve different techniques and instruments, there is no evidence for significant differences in the results obtained between closed and open hemorrhoidectomies. 6,7 In any surgical management of hemorrhoids, postoperative pain is the most common complaint. 8 In particular, internal sphincter spasm is usually associated with pain.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital stay in our study in group A was 2.10±0.40 days whereas hospital stay in group B was 1.94±1.16 p value 0.78 (not significant). Hosh et al (19) showed that hospital stay was more in open haemorrhoidectomy while Gencosmanoglu et al (20) showed opposite results.…”
Section: Introductionmentioning
confidence: 99%
“…1 It can be performed by the open or closed method. 2 , 3 In Europe, the Milligan-Morgan method is more commonly in use, while in the United States the closed haemorrhoidectomy method, as illustrated by Ferguson and Heaton, is a common and traditional method. 2 - 4 Closed haemorrhoidectomy is supposed to be less painful method and results in rapid wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…2 , 3 In Europe, the Milligan-Morgan method is more commonly in use, while in the United States the closed haemorrhoidectomy method, as illustrated by Ferguson and Heaton, is a common and traditional method. 2 - 4 Closed haemorrhoidectomy is supposed to be less painful method and results in rapid wound healing. 2 , 5 However, a disagreement is still there concerning these two techniques of management with regards to postoperative pain and complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation